A spatially resolved ratiometric electrochemiluminescence immunosensor for myoglobin detection using Au@Ag2S as signal amplification tags. (30th August 2022) - Chen, Chen; Ma, Jin-Xin; Wang, Hui; Liu, Hui-Qiao; Ren, Shu-Wei; Cao, Jun-Tao; Liu, Yan-Ming
Abstract : A spatially resolved ratiometric ECL immunosensor for myoglobin detection was developed via resonance energy transfer for signal amplification. Abstract : It is promising to devise a signal-amplified ratiometric electrochemiluminescence (ECL) sensing platform owing to the eliminated external interference and increased analysis reliability in complex samples. Herein, a spatially resolved ratiometric ECL immunosensor for myoglobin (Myo) detection was developed via resonance energy transfer (RET) for signal amplification. In the ECL system, Ru(bpy)3 2+ -conjugated silica nanoparticles (Ru(bpy)3 2+ @RuSi NPs) and sulfur quantum dots (SQDs) used as the potential-resolved ECL emitters were modified on two spatially resolved electrodes, respectively. Au@Ag2 S NPs with a wide light absorption range could serve as perfect acceptors of Ru(bpy)3 2+ @RuSi NPs, between which an effective RET could occur. For Myo detection, the signal from the Ru(bpy)3 2+ @RuSi NP-modified electrode for Myo with various concentrations acted as the working signal (ECLanode ) and that from the SQD electrode for Myo with fixed concentration served as a reference signal (ECLcathode ). Owing to the steric hindrance and effective RET between Ru(bpy)3 2+ @RuSi NPs and Au@Ag2 S NPs, the working signal presented a great decrease in the presence of Myo. The ratio of ECLanode to ECLcathode showed a linear relationship with the logarithm of the Myo concentration in the range from 1.0 × 10 −13 to 1.0 × 10 −7 g mL −1 . The limit of detection of the fabricated biosensor was 5.0 × 10 −14 g mL −1 . Moreover, it continued to show favorable detection results in human serum samples with recoveries ranging from 83.0 to 110%. The RET and ratiometric strategy on the spatially resolved platform endow the method with the merits of high selectivity, sensitivity, and accuracy and it can be envisioned that the method would provide a general tool for biomarker analysis.